Pengendalian Serangan Hama Helopeltis bradyi pada Tanaman Eukaliptus dengan Berbagai Jenis Bahan Aktif Insektisida di Laboratorium - Suhandi; Setiaji Heri Saputro; Surodjo Taat Andayani (Jurnal Wana Tropika, 2026)
The damage to eucalyptus plants caused by one species of Helopeltis, namely Helopeltis bradyi, is one of the main factors hindering the growth process and causing the death of eucalyptus plants in the Industrial Forest area at PT. Toba Pulp Lestari. Chemical control using insecticides with specific active ingredients is one way to prevent and reduce damage to eucalyptus plants caused by these pests. This study was conducted to determine the effect of various types of insecticide active ingredients on the control of Helopeltis bradyi pests. This study used a Randomized Completely Block Design (RCBD) with in-vivo laboratory testing using one treatment factor that is different types of insecticides with active ingredients consisting of five levels: control, insecticides with the active ingredients alfa-cypermethrin, buprofezin, dimehipo, and nitenpyram. The parameters observed were mortality rate (pest death) and severity of plant shoot attack with an observation period of 3 days. The data obtained were analyzed using analysis of variance and Duncan's Multiple Range Test (DMRT) to test for significant differences between each treatment. Based on the results of the study, it was found that the use of different types of insecticide active ingredients had an effect on the mortality rate (pest death) and severity on plant shoots by the Helopeltis bradyi pest. The insecticide active ingredients Nitenpyram and Alpha-cypermethrin showed the highest mortality rates and were able to significantly reduce the severity of damage to plant shoots by the Helopeltis bradyi pest.